2017
DOI: 10.1515/sem-2016-0074
|View full text |Cite
|
Sign up to set email alerts
|

Staying over-optimistic about the future: Uncovering attentional biases to climate change messages

Abstract: For more information, including our policy and submission procedure, please contact the Repository Team at: usir@salford.ac.uk. AbstractThere is considerable concern that the public are not getting the message about climate change. One possible explanation is 'optimism bias', where individuals overestimate the likelihood of positive events happening to them and underestimate the likelihood of negative events. Evidence from behavioural neuroscience suggest that this bias is underpinned by selective information… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…Specifically, one study using eye tracking found that people with high trait optimism spent significantly less time attending to any information related to climate change, with particularly low fixation times if the arguments about climate change conveyed “bad news” (Beattie, Marselle, McGuire, & Litchfield, 2017). The authors also found that people with high dispositional optimism more likely recalled the arguments in terms of a debate between two opposing positions (as opposed to framing it as clear evidence) and were more confident that the consequences of climate change would not affect them personally (Beattie et al, 2017). Likewise, a study applying the belief-updating framework to information about climate change demonstrated that people who do not believe in the concept of man-made climate change updated their beliefs more toward good news (suggesting that the global rise of the average temperature may not be as dramatic as predicted) than toward bad news (suggesting that the global rise of the average temperature is even more dramatic than predicted; Sunstein, Bobadilla-Suarez, Lazzaro, & Sharot, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, one study using eye tracking found that people with high trait optimism spent significantly less time attending to any information related to climate change, with particularly low fixation times if the arguments about climate change conveyed “bad news” (Beattie, Marselle, McGuire, & Litchfield, 2017). The authors also found that people with high dispositional optimism more likely recalled the arguments in terms of a debate between two opposing positions (as opposed to framing it as clear evidence) and were more confident that the consequences of climate change would not affect them personally (Beattie et al, 2017). Likewise, a study applying the belief-updating framework to information about climate change demonstrated that people who do not believe in the concept of man-made climate change updated their beliefs more toward good news (suggesting that the global rise of the average temperature may not be as dramatic as predicted) than toward bad news (suggesting that the global rise of the average temperature is even more dramatic than predicted; Sunstein, Bobadilla-Suarez, Lazzaro, & Sharot, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Some evidence suggests that this, in addition to various other factors, may be due to the optimistic bias when confronted with bad news. Specifically, one study using eye tracking found that people with high trait optimism spent significantly less time attending to any information related to climate change, with particularly low fixation times if the arguments about climate change conveyed "bad news" (Beattie, Marselle, McGuire, & Litchfield, 2017). The authors also found that people with high dispositional optimism more likely recalled the arguments in terms of a debate between two opposing positions (as opposed to framing it as clear evidence) and were more confident that the consequences of climate change would not affect them personally (Beattie et al, 2017).…”
Section: Societal Implicationsmentioning
confidence: 99%
“…However, more research is urgently required to determine the amenability of thought processes to change (e.g. the correction of biases) as evidence suggests that the acceleration of climate change can be reinforced by a collection of different psychological phenomena, including the single action bias (Weber, 1997), optimism bias (Beattie et al, 2017), moral licensing effects (Klöckner et al, 2013), rebound effects (Binswanger, 2001) and the negative footprint illusion (Gorissen & Weijters, 2016;Holmgren et al, 2018b;Kabanshi, 2020).…”
mentioning
confidence: 99%
“…Some cognitive biases have been found to influence humans to accept or deny climate change. This ranges from Optimism bias (the over estimation of positive events happening - Beattie et al, 2017) to Loss aversion (the idea that protecting against losses is more important that acquiring equivalent gains -Bowman, 2011), and Perception biases (the limitation to process information about events that have not yet happened -Mazutis and Eckardt, 2017).…”
Section: Cognitive Biasmentioning
confidence: 99%
“…While different cognitive biases have been investigated as prerequisites to (not) act on climate change, poor communication styles and argumentation were also found to be relevant factors that could undermine effective action in this context (Johnson and Levin, 2009). Hence, social scientists have started to research different methods to overcome cognitive biases to achieve more effective communication strategies regarding climate change (Beattie et al, 2017). Bowman (2011) noted that policy on climate change stands a better chance of success if cognitive biases are taken into account when formulating and communicating policy.…”
Section: Cognitive Biasmentioning
confidence: 99%